PENGARUH PENDEKATAN MULTISENSORI TERHADAP KECERDASAN LOGIKA-MATEMATIKA PADA ANAK KELOMPOK A DI TAMAN KANAK-KANAK KABUPATEN KENDAL - Fiani, Eva Agus (Indonesian Journal of Early Childhood Education Studies, 2012)
Logical-mathematical intelligence is important to be taught by teacher to kindergarten children so that they have skill in solving si mple problems in daily life. Multisensory approach emphasizes the principles of teaching through visual, auditory, kinesthetic and tactile (VAKT). The purpose of this study was to determine whether there is influence multisensory approach to the  logical -mathematical intelligence  in kindergarten children. Paired t-test calculation results between the pretest and posttest the experimental group there was an increase by an average of 21.65 from 14.95 average pretest to 36.6 posttest. Paired t-test calculation results between the pretest and posttest control group contained an average increase of 11.3 from an average of 16.9 to 28.2 pretest posttest.  Independent  t-test  results  of  the  pretest  experimental  and  control  groups  showed  no  significant differences as having value Sig. (2-tailed) > 0.05 is 0.631 > 0.05. That is logical-mathematical intelligence levels in children before using multisensory approach is same. Independent t-test results posttest experimental and control groups showed no significant difference because it has the Sig. (2-tailed) < 0.05 is 0.02 < 0.05. Based  on  the  description,  it  was  concluded  that  multisensory  approach  gives  significant  effect  on  logic - mathematical intelligence in kindergarten children. The results show that multisensory approach gives significant effect on logic-mathematical intelligence inkindergarten children. Average of logical-mathematical intelligence of students in using multisensory approach is higher than the averageof logical-mathematical intelligence of students who  do not use  logic-mathematical approach. It is suggested to teachers in usingmultisensory approach to improve logical-mathematical intelligence in kindergarten children. Limitations of this study is the assistanceof teachers, child emotional factor, and time constraints.